«О слово рідне, хто без тебе я?» (About the epoch’s style and Dmytro Pavlychko’s individual style) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2012)
The article deals with individual uniqueness of writer in the selection of the verbal means of the world scene’s recreation; with the peculiarities of realization of the belletristic style’s opportunities according  to the esthetic author’s intrntion.
Keywords: author’s; linguistic personality; idiostyle; belletristic text